The Importance of Enacting Indonesian Data Protection Law as a Legal Responsibility for Data Leakage - Edelweiss Premaulidiani Putri; Aroma Elmina Martha (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The disclosure of digital development and the openness of many online transactions often lead to data leakage. Furthermore, digital development on the one hand, provides benefits to the digital economy and at the same time also led to the new impact or threat to the conventional economy from the aspect of cyber-security vulnerabilities to harm customer information and challenge the concept of privacy. The lack of government consents the data protection against the 1945 Constitution. This study aims to propose accelerating the Indonesian Personal Data Protection Bill by The House of Representative Council (DPR). This study uses a normative juridical method with a statute approach, the data used is secondary data consisting of primary and secondary legal material. The result shows the urgency of designing new regulation prior to tackling the issue on data leakage and maintaining the confidentiality of the personal data of Indonesian citizens. Through the enacting PDP Law will benefit the stakeholders, the data owner and further recognition by other countries.